EFEKTIVITAS STRATEGI PEMASARAN XIAOMI MELALUI SOSIAL MEDIA DI KABUPATEN JEMBER - Musyaffa', Musyaffa'; Maryani, Maryani; Mufidah, Hayatul; Sutjahyo, Sutjahyo; Qomariah, Nurul (Fakultas Ekonomi dan Bisnis, 2022)
The smartphone market in Jember Regency has experienced rapid growth in recent years. Xiaomi, as one of the leading smartphone brands, has a big opportunity to increase its sales in this region. This research aims to analyze effective digital marketing strategies to increase sales of Xiaomi products in Jember Regency. This research uses qualitative methods with a case study on Xiaomi. Data was collected through interviews with key informants, observation and document analysis. The aim of this research is to determine the effectiveness of Xiaomi's marketing strategy in Jember Regency in increasing sales. The research results show that effective digital marketing strategies to increase sales of Xiaomi products in Jember Regency include social media optimization, influencer marketing, digital advertising, content marketing, e-commerce. This research shows that an effective digital marketing strategy can help Xiaomi increase its sales in Jember Regency. Implementing appropriate and measurable strategies can help Xiaomi achieve its market target in this region.